Ventajas y desventajas del procedimiento de la contratación pública mediante la Subasta Inversa en Colombia (2013)
With the realization and analysis of this official paper it pretends identify the economic and technical impacts generated in the Government engagement in Colombia, in exercise to the abbreviated selection mode, reverse auction procedure. The analysis covers the period from 2002 until today, through all the reforms, reached to the last made in 2012, which generated a massive accomplishment of these contractual processes, separating a little of the benefit cost, it means, unknown, this type of contract to have the unique criterion of choosing the price is going to be sacrificed the quality of the benefits and services to acquire.